Exports and International Logistics - Behar, Alberto; Manners, Phil; Nelson, Benjamin (2012)
Do better international logistics reduce trade costs, raising a developing country's exports? Yes, but the magnitude of the effect depends on the country's size. The authors apply a gravity model that accounts for firm heterogeneity and multilateral resistance to a comprehensive new international logistics index. A one-standard deviation improvement in logistics is equivalent to a 14 percent reduction in distance. An average-sized developing country would raise exports by about 36 percent. Most countries are much smaller than average however, so the typical effect is 8 percent. This difference is chiefly due to multilateral resistance: it is bilateral trade costs relative to multilateral trade costs that matter for bilateral exports, and multilateral resistance is more important for small countries.